1994
DOI: 10.1302/0301-620x.76b3.8175847
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroplasty in haemodialysis patients

Abstract: We retrospectively reviewed 17 hip arthroplasties in 15 patients having haemodialysis for chronic renal failure. The duration of haemodialysis before the operation averaged 8.6 years and the average age of the patients was 61 years. All patients were followed for more than two years (mean 4.6 years). Six arthroplasties in four patients had failed due to loosening, and one of these patients died from undiagnosed infection of both hips at 7.6 years after the operation. General skeletal abnormalities caused by ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
2
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 0 publications
1
37
2
3
Order By: Relevance
“…The findings were similar with the previous studies on the chronic diseases [13][14][15]. This study suggests that individuals with arthritis should be targeted for specific health behavioral intervention to prevent the progression of arthritis [16][17]. Based on the results obtained by the study, it is anticipated that this paper may be used as basic data for developing and interventing health promotion behavior for the arthroplasty patients.…”
Section: Discussionsupporting
confidence: 88%
“…The findings were similar with the previous studies on the chronic diseases [13][14][15]. This study suggests that individuals with arthritis should be targeted for specific health behavioral intervention to prevent the progression of arthritis [16][17]. Based on the results obtained by the study, it is anticipated that this paper may be used as basic data for developing and interventing health promotion behavior for the arthroplasty patients.…”
Section: Discussionsupporting
confidence: 88%
“…29 One study reported a complication rate of 35% and did not recommend THR for haemodialysis patients. 21 Although uncemented THR has achieved promising results in recent years, 19,20,37 it is recommended that renal transplantation be performed before THR for those eligible. 36 In 11 studies of renal transplant patients, all concluded that THR was a good option.…”
Section: Discussionmentioning
confidence: 99%
“…A higher incidence of loosening and more progressive and severe osteolysis in hemodialysis patients who have low physical activity cannot be attributed only to weakness of bone, as reported (Campistol et al 1990, Naito et al 1994), but probably to unknown biological reactions to the amyloid deposition in the interface. We found little evidence of wear particles or cellular reaction in the interface.…”
Section: Bengt Mjobergmentioning
confidence: 72%